EVALUASI DALAM PROSES PEMBELAJARAN - IDRUS L (Adaara: Jurnal Manajemen Pendidikan Islam, 2019)
Abstract: Learning evaluation is an activity to collect data and information about students' learning abilities, to assess how far the learning program has been running, and also as a tool to determine whether the educational objectives and learning process in developing science have taken place as they should. In addition, the evaluation also aims to determine the level of student achievement in a learning process, as well as to understand students the extent to which they can provide assistance to the shortcomings of students, with the aim of placing students in a learning situation that is more appropriate to their ability level. The function of learning evaluation is to help the process, progress and development of students' learning outcomes on an ongoing basis, and at the same time be able to know the abilities and weaknesses of students in a particular field of study, while also being able to provide information to parents/guardians of students regarding class ranking or determining graduation of participants students. The evaluation tool requirements are validity, effectiveness, different items and objectivity.